Survival in Out-of-Hospital Cardiac Arrest After Standard Cardiopulmonary Resuscitation or Chest Compressions Only Before Arrival of Emergency Medical Services: Nationwide Study During Three Guideline Periods. Issue 23 (4th June 2019) - Riva, Gabriel; Ringh, Mattias; Jonsson, Martin; Svensson, Leif; Herlitz, Johan; Claesson, Andreas; Djärv, Therese; Nordberg, Per; Forsberg, Sune; Rubertsson, Sten; Nord, Anette; Rosenqvist, Mårten; et al.
Abstract : Background: In out-of-hospital cardiac arrest, chest compression–only cardiopulmonary resuscitation (CO-CPR) has emerged as an alternative to standard CPR (S-CPR), using both chest compressions and rescue breaths. Since 2010, CPR guidelines recommend CO-CPR for both untrained bystanders and trained bystanders unwilling to perform rescue breaths. The aim of this study was to describe changes in the rate and type of CPR performed before the arrival of emergency medical services (EMS) during 3 consecutive guideline periods in correlation to 30-day survival. Methods: All bystander-witnessed out-of-hospital cardiac arrests reported to the Swedish register for cardiopulmonary resuscitation in 2000 to 2017 were included. Nonwitnessed, EMS-witnessed, and rescue breath–only CPR cases were excluded. Patients were categorized as receivers of no CPR (NO-CPR), S-CPR, or CO-CPR before EMS arrival. Guideline periods 2000 to 2005, 2006 to 2010, and 2011 to 2017 were used for comparisons over time. The primary outcome was 30-day survival. Results: A total of 30 445 patients were included. The proportions of patients receiving CPR before EMS arrival changed from 40.8% in the first time period to 58.8% in the second period, and to 68.2% in the last period. S-CPR changed from 35.4% to 44.8% to 38.1%, and CO-CPR changed from 5.4% to 14.0% to 30.1%, respectively. Thirty-day survival changed from 3.9% to 6.0% to 7.1% in the NO-CPR group, from 9.4% to 12.5% to 16.2% in the S-CPR group, and from 8.0% to 11.5% to 14.3% in the CO-CPR group. For all time periods combined, the adjusted odds ratio for 30-day survival was 2.6 (95% CI, 2.4–2.9) for S-CPR and 2.0 (95% CI, 1.8–2.3) for CO-CPR, in comparison with NO-CPR. S-CPR was superior to CO-CPR (adjusted odds ratio, 1.2; 95% CI, 1.1–1.4). Conclusions: In this nationwide study of out-of-hospital cardiac arrest during 3 periods of different CPR guidelines, there was an almost a 2-fold higher rate of CPR before EMS arrival and a concomitant 6-fold higher rate of CO-CPR over time. Any type of CPR was associated with doubled survival rates in comparison with NO-CPR. These findings support continuous endorsement of CO-CPR as an option in future CPR guidelines because it is associated with higher CPR rates and overall survival in out-of-hospital cardiac arrest. Abstract : Supplemental Digital Content is available in the text.